# Solve Using the Square Root Property x(x-3)=70 x(x-3)=70
Simplify x(x-3).
Apply the distributive property.
x⋅x+x⋅-3=70
Simplify the expression.
Multiply x by x.
x2+x⋅-3=70
Move -3 to the left of x.
x2-3x=70
x2-3x=70
x2-3x=70
Move 70 to the left side of the equation by subtracting it from both sides.
x2-3x-70=0
Factor x2-3x-70 using the AC method.
Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -70 and whose sum is -3.
-10,7
Write the factored form using these integers.
(x-10)(x+7)=0
(x-10)(x+7)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
x-10=0
x+7=0
Set the first factor equal to 0 and solve.
Set the first factor equal to 0.
x-10=0
Add 10 to both sides of the equation.
x=10
x=10
Set the next factor equal to 0 and solve.
Set the next factor equal to 0.
x+7=0
Subtract 7 from both sides of the equation.
x=-7
x=-7
The final solution is all the values that make (x-10)(x+7)=0 true.
x=10,-7
Solve Using the Square Root Property x(x-3)=70     